Risk factors of nasal carriage of Staphylococcus aureus and methicillin-resistant Staphylococcus aureus among health care staff in a teaching hospital in central Saudi Arabia - Al-Humaidan, Ohoud S. (Saudi Med J, 2015)
OBJECTIVES: To investigate possible risk factors of Staphylococcus aureus (S. aureus) and methicillin-resistant S. aureus (MRSA) nasal carriage associated with various health troubles among healthcare workers (HCWs) at King Khalid University Hospital (KKUH). METHOD: This prospective study was conducted between May 2012 and January 2013 in KKUH, Riyadh, Saudi Arabia. A total of 200 nasal swabs were collected from HCWs. Identification was carried out based on morphology, Gram stain, catalase and coagulase test, Staphaurex PlusH test, chromogenic medium, oxacillin, and cefoxitin test using disc diffusion method. Characterization was carried out using disk diffusion method and E-test. Polymerase chain reaction was carried out to confirm using GeneXpert(®) Dx System (Cepheid) to detect mecA gene. RESULTS: Among the 200 isolates, 80 (40%) were S. aureus carriers, and 36 (18%) of all HCWs were identified as MRSA carriers. There was a significant difference of S. aureus according to gender with male carriers (p=0.012), occupation particularly among nurses (p=0.006), and duration of working years in the hospital among 4-6 years group (p=0.002). Moreover, none of the risk factors assessed were significantly associated with the carriage rate of MRSA (p>0.05). CONCLUSION: The current study revealed that nursing staff was the potential colonizers of S. aureus and MRSA compared with other HCWs. Regular screening of carriers is required for prevention of nosocomial infections.